Analisis Pengaruh Port Service Quality Terhadap Customer Loyalty Dimediasi Oleh Customer Experience Dan Customer Satisfaction di Terminal Peti Kemas Tanjung Priok - Amanda, Anggi Nurul; Raharjo, Sri; Abdurachman, Edi; Setiawan, Edhie Budi; Arubusman, Dian Artanti (Dinasti Research, 2025)
This study investigates the relationship between Port Service Quality (PSQ) and Customer Loyalty (CL), taking into account the mediating roles of Customer Experience (CE) and Customer Satisfaction (CS) in the context of import activities at the Tanjung Priok Container Terminal. The research is motivated by the declining competitiveness of Tanjung Priok Port in comparison to other major ports such as Tanjung Perak, and the growing necessity to retain customer loyalty amid rising expectations for logistics efficiency and digital transformation in port operations. A critical strategic factor in enhancing port service efficiency lies in the optimization of port administration functions, particularly those carried out by the Harbormaster and Port Authority Office (KSOP). KSOP plays a key role in overseeing and facilitating port operations, including coordination in traderelated processes such as customs clearance and quarantine. These administrative procedures have been significantly streamlined through the adoption of the Single Submission Management (SSM) system—an integrated electronic platform that enables faster, cross-agency document processing. Employing a quantitative approach, this study utilizes Partial Least Squares–Structural Equation Modeling (PLS-SEM) to analyze data collected from 200 active importers operating at Tanjung Priok Port. The research model considers PSQ as the independent variable, CE and CS as mediating variables, and CL as the dependent variable. The findings demonstrate that PSQ has a statistically significant effect on CL, both directly and indirectly through the mediation of CE and CS. These results underscore the importance of service quality enhancement as a means to improve customer experience and satisfaction, ultimately fostering greater customer loyalty. Strengthening digital infrastructure and inter-agency coordination through systems such as SSM is thus essential for improving port competitiveness and long-term customer retention.